INOVASI PELAYANAN PUBLIK MELALUI APLIKASI SMART CAMPUS DATA BASE (SCDB) DI KAMPUS INSTITUT PEMERINTAHAN DALAM NEGERI - Putri, Lusy Riadina (Jurnal Teknologi dan Komunikasi Pemerintahan, 2021)
Service is one of the duties and functions of the profession of the State Civil Servant (ASN), as a state servant and ASN community servant has several main tasks and functions, one of which is public service. Public services become the main face of the Government as the organizer of bureaucracy, good or bad public services from the Government will get a direct assessment by the public as consumers of public services. The Institute of Government of Home Affairs (IPDN) as one of the government agencies to made ASN cadres of Home Affairs government creates a public service innovation through the Smart Campus Data Base (SCDB) application as one of the containers of public services today and services for IPDN academic community interns. SCDB application is the provision of the latest data or databases and electronic information that is integrated online and can be easily accessed in general, especially by the academic community to obtain data and information about IPDN. The research method used is a descriptive type Qualitative research method. The existence of technological changes in the industrial era 4.0 is getting faster, to be able to keep up with the development of this technology IPDN must have a database where all data or information related to IPDN can be accessed directly through SCDB, the constraints in the human resources admin data manager from each unit/part in IPDN, especially in the field of informatics engineering as the person in charge of data input, IPDN needs for good cooperation for the integration of data in IPDN can run optimally to provide smoothness of the general public and academic community in accessing various information needed through the Smart Campus Data Base (SCDB) Application. Keywords: Public Service, SCDB Application, Institute of Internal Government